Mortality Associated With Respiratory Syncytial Virus, Bronchiolitis, and Influenza Among Infants in the United States: A Birth Cohort Study From 1999 to 2018. (16th April 2022) - Reichert, Heidi; Suh, Mina; Jiang, Xiaohui; Movva, Naimisha; Bylsma, Lauren C; Fryzek, Jon P; Nelson, Christopher B
Abstract: Background: Infant mortality due to respiratory syncytial virus (RSV) in the United States is not well understood. Methods: From 1999 to 2018, RSV, bronchiolitis, and influenza deaths were described for infants <1 year using linked birth/death datasets from the National Vital Statistics System. Mortality was described overall and by infant birth and death characteristics. Bronchiolitis was included as the plausible upper limit of RSV, while influenza served as a comparator. Results: Total infant deaths were 561 RSV, 1603 bronchiolitis, and 504 influenza, and rates were 6.9 (95% confidence interval [CI], 6.4–7.5), 19.8 (95% CI, 18.9–20.8), and 6.2 (95% CI, 5.7–6.8) per 1 000 000 live births, respectively. The highest RSV rates were observed among <29 weeks' gestational age infants (103.5; 95% CI, 81.8–129.1), American Indian/Alaskan Native (20.3; 95% CI, 11.6–33.0), and Medicaid-insured (7.3; 95% CI, 5.9–8.9). However, RSV mortality burden was greatest in full-term (53.7%), white (44.9%), and Medicaid-insured (61.7%) infants. Deaths outside the inpatient setting were 21% and 54% for RSV and bronchiolitis; more Medicaid- (58%) and other/unknown-insured (69%) infants with bronchiolitis died outside of the inpatient setting, compared to privately insured infants (48%) ( P  = .0327). Conclusions: These national estimates emphasize the importance of considering all infants across all healthcare settings when describing RSV mortality.